Toward Climate-Resilient Development in Nigeria - Cervigni, Raffaello; Valentini, Riccardo; Santini, Monia (Washington, DC: World Bank, 2013)
This book analyzes the risks to Nigeria's development prospects that climate change poses to agriculture, livestock, and water management. These sectors were chosen because they are central to achieving the growth, livelihood, and environmental objectives of Vision 20: 2020; and because they are already vulnerable to current climate variability. Since other sectors might also be affected, the findings of this research provide lower-bound estimates of overall climate change impacts. Agriculture accounts for about 40 percent of Nigeria's Gross Domestic product (GDP) and employs 70 percent of its people. Because virtually all production is rain-fed, agriculture is highly vulnerable to weather swings. It alerts us that increases in temperature, coupled with changes in precipitation patterns and hydrological regimes, can only exacerbate existing vulnerabilities. The book proposes 10 practical short-term priority actions, as well as complementary longer-term initiatives, that could help to mitigate the threat to vision 20: 2020 that climate change poses. Nigeria's vision can become a reality if the country moves promptly to become more climate-resilient. Climate variability is also undermining Nigeria's efforts to achieve energy security. Though dominated by thermal power, the country's energy mix is complemented by hydropower, which accounts for one-third of grid supply. Because dams are poorly maintained, current variability in rainfall results in power outages that affect both Nigeria's energy security and its growth potential. In particular, climate models converge in projecting that by mid-century water flows will increase for almost half the country, decrease in 10 percent of the country, and be uncertain over one-third of Nigeria's surface. The overall feasibility of Nigeria's hydropower potential is not in question. On grounds of energy diversification and low carbon co-benefits, exploiting the entire 12 gigawatts (GW) of hydropower potential should be considered. Nigeria has a number of actions and policy choices it might consider for building up its ability to achieve climate-resilient development.